Big data in the food supply chain: The technological, organisational and environmental factors that play a role - Jokonya, Osden; Taff, Jade (New Agenda: SA Journal of Social and Economic Policy, 2024)
The fourth industrial revolution has redesigned the future of food production and transformed the food supply chain. This advancement and evolution of digitalisation has enabled organisations to modify business models and processes resulting in new and increased revenue and enhanced value-offering opportunities. This has meaningfully altered and advanced the adoption of big data technologies in organisations. OSDEN JOKONYA argues that the adoption of big data in the food supply chain is important to African food systems and analyses the factors that affect its adoption.